In situ calibration of the Gamma Reaction History instrument using reference samples (“pucks”) for areal density measurements - Hoffman N.M.; Herrmann H.W.; Kim Y.H.; Hsu H.H.; Horsfield C.J.; Rubery M.S.; Wilson D.C.; W. Stoeffl W.; Young C.S.; Mack J.M.; Miller E.K.; Grafil E.; et al. (EPJ Web of Conferences, 2013)
The introduction of a sample of carbon, for example a disk or “puck”, near an imploding DT-filled capsule creates a source of 12C gamma rays that can serve as a reference for calibrating the response of the Gamma Reaction History (GRH) detector [1]. Such calibration is important in the measurement of ablator areal density ⟨ρR⟩abl in plastic-ablator DT-filled capsules at OMEGA [2], by allowing ⟨ρR⟩abl to be inferred as a function of ratios of signals rather than from absolute measurements of signal magnitudes. Systematic uncertainties in signal measurements and detector responses therefore cancel, permitting more accurate measurements of ⟨ρR⟩abl.